Theories of truth in Chinese philosophy : a comparative approach - McLeod, Alexus (Critical inquiries in comparative philosophy., 2015)
This book examines different views on the concept of truth in early Chinese philosophy, and considers a variety of theories of truth in Chinese and comparative thought.